Long noncoding RNA NEAT1 promotes tumorigenesis in H. pylori gastric cancer by sponging miR‐30a to regulate COX‐2/BCL9 pathway. Issue 6 (16th August 2021) - Rao, Xiwu; Liu, Xuan; Liu, Ningning; Zhang, Yi; Zhang, Zhaozhou; Zhou, Lihong; Han, Gang; Cen, Rong; Shi, Nuolin; Zhu, Huirong; Gong, Hangjun; Huang, Chen; et al.
Abstract: Background: Helicobacter pylori ( H .  pylori ) is a carcinogenic factor for gastric cancer. Our previous study demonstrated that H .  pylori decreased the expression of micro‐RNA (miRNA)‐30a to promote the tumorigenesis of gastric cancer. However, the upstream regulatory molecules of miR‐30a are not well elucidated. In this study, we found the long non‑coding RNA (lncRNA) nuclear paraspeckle assembly transcript 1 ( NEAT1 ) may sponge miR‐30a to regulate COX‐2/BCL9 pathway. Methods: The expression of NEAT1 was detected in gastric cancer tissues and tumor‐adjacent tissues by fluorescence in situ hybridization (FISH) analysis and RT‐qPCR. LncRNA‐miRNA interaction networks were constructed using the RNAhybrid and starBase v.2.0. and then validated using a dual‐luciferase reporter assay. The effects of NEAT1 dysregulation on the proliferative, migratory, and invasive abilities of H .  pylori filtrate‐infected gastric cancer cells were observed by cell counting kit‐8 (CCK‐8), colony formation, wound healing test, and transwell assays. Western blot and RT‐qPCR were performed to detect protein and RNA expression. Immunohistochemistry (IHC) was carried out to analyze the localization and expression of COX‐2 and BCL9. Results: FISH and RT‐qPCR demonstrated that the expression of NEAT1 was up‐regulated in gastric cancer tissues, especially in H .  pylori ‐infected gastric cancer tissues, and the expression of NEAT1 was negatively correlated with miR‐30a (miR‐30a‐3p and miR‐30a‐5p). The upregulation of NEAT1 enhanced proliferation, migration, and invasion of H .  pylori filtrate‐infected gastric cancer cells, while the downregulation of NEAT1 decreased these abilities, and miR‐30a could reverse the effect of NEAT1 on these abilities. The dual‐luciferase reporter assay identified that NEAT1 directly targeted miR‐30a (miR‐30a‐3p and miR‐30a‐5p). Because miR‐30a (miR‐30a‐3p and miR‐30a‐5p) negatively regulates the expression of downstream COX‐2 and BCL9, NEAT1 was identified to upregulate indirectly the expression of COX‐2 and BCL9. IHC showed that the expression of COX‐2 and BCL9 was increased in H .  pylori gastric cancer tissues. Conclusion: The study demonstrated that lncRNA NEAT1 may act as a promoter of tumorigenesis in H .  pylori gastric cancer, by sponging miR‐30a (miR‐30a‐3p and miR‐30a‐5p) to regulate the COX‐2/BCL9 pathway.